Transmedia in Higher Education. A qualitative research - Gomero, Giancarlo (2023)
SciVal Topics Metrics Funding details Abstract Introduction: The relation between education and transmedia storytelling has been developed through diverse paths and based on different criteria, such as genre, source, temporality, and the given education level observed. The present study aims to contribute to the understanding of ongoing processes that transmedia storytelling is going through, and its space in higher education on both sides of the Atlantic. Methodology: With this goal, a structured interview was designed and validated, addressing 21 academic directors and experts in the field of communication and interactive media in higher education in Latin America, Spain, and Portugal. Results: The findings show a current map of transmedia storytelling in universities through the observation of its human and material resources, as well as evidencing discussions on terminological and conceptual points of view and, consequently, their instrumentalization in praxis. Discussion and Conclusions: These findings also show a progressive advance in the presence of transmedia storytelling higher education curriculums, and an academic void, pointed out by faculty members, regarding concrete training initiatives from their university centers, aimed at them as current teachers and researchers.